Is Sudden Hearing Loss Associated with Atherosclerosis? - Mohsen Rajati (Iranian Journal of Otorhinolaryngology, 2016)
Introduction: Sudden sensorineural hearing-loss (SSNHL) patients constitute approximately 2–3% of referrals to ear, nose and throat (ENT) clinics. Several predisposing factors have been proposed for this condition; one of which is vascular disorders and perfusion compromise. In this research the atherosclerotic changes and their known risk factors are studied in SSNHL patients.   Materials and Methods: Thirty SSNHL patients and 30 controls were evaluated with regard to cardiovascular risks including history, heart examination, blood pressure, body mass index, waist circumference, electrocardiogram, blood sugar, triglycerides, cholesterol, high-sensitivity C-reactive protein (HSCRP); also, carotid artery color Doppler study was undertaken to measure intima media thickness(IMT).   Results: IMT and HSCRP showed an increased risk in the case group compared with the controls (P= 0.005 & P=0.001). However, waist circumference, history of smoking, fasting blood sugar, lipid profile, and electrocardiogram revealed no significant difference between the two groups. Interestingly, blood pressure and body mass index were higher in the controls in this study.   Conclusion:  Sudden sensorineural hearing loss may be associated with subclinical atherosclerosis.